PERFORMANCE MEASUREMENT MODEL ANALYSIS OF LOW COST FLATS MANAGEMENT IN SURABAYA - Arining Christanti; Putu Artama Wiguna; Retno Indryani (Journal of Civil Engineering, 2017)
The absence of parameter in assessing the low cost flats performance causing lack of evaluation and monitoring on low cost flats management. This is often generates difficulty for manager to determine solution on management problems. Therefore, this research aims to obtain performance measurement models that can be used as parameter of assessment in the evaluation and monitoring of low cost flats management in Surabaya. Stages of this research are formulation of the model according to the literature review and the existing condition, assessment of performance management, and fitness model evaluation. Results of the research showed performance measurement model with variable weights ratings as follows: effectiveness and efficiency (34.6%), institutional suitability and tenancy (26.5%), the risk of legal compliance (19%), physical condition (10.9%), sustainability (5.4%) and impact (3.5%). Based on performance assessment of 8 low cost flats buildings as a representative sample of low cost flats in Surabaya, found that 62.5% low cost flats had good performance and 37.5% low cost flatslow cost flats had sufficient performance. From the fitness model evaluation, known that the performance measurement models is relevant enough to be used as assessment parameter of low cost flats management in Surabaya